2020
DOI: 10.3390/s20092698
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and Robust Floor Positioning in Complex Indoor Environments

Abstract: With the widespread development of location-based services, the demand for accurate indoor positioning is getting more and more urgent. Floor positioning, as a prerequisite for indoor positioning in multi-story buildings, is particularly important. Though lots of work has been done on floor positioning, the existing studies on floor positioning in complex multi-story buildings with large hollow areas through multiple floors still cannot meet the application requirements because of low accuracy and robustness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It is possible that future studies could capitalize on ‘smart home’ environments, embedding multi-camera systems (‘living labs’) [ 14 ], which could potentially deliver a new gold-standard measure of FOG. Furthermore, the field should strive to assess these video recording methods alongside other technologies, such as marker-less motion capturing, mobile video-systems, and Wi-Fi motion detection software [ 15 ] to determine the optimal conditions to obtain the most useful data for modeling.…”
Section: Standardising Definitions Assessments and Measurementsmentioning
confidence: 99%
“…It is possible that future studies could capitalize on ‘smart home’ environments, embedding multi-camera systems (‘living labs’) [ 14 ], which could potentially deliver a new gold-standard measure of FOG. Furthermore, the field should strive to assess these video recording methods alongside other technologies, such as marker-less motion capturing, mobile video-systems, and Wi-Fi motion detection software [ 15 ] to determine the optimal conditions to obtain the most useful data for modeling.…”
Section: Standardising Definitions Assessments and Measurementsmentioning
confidence: 99%
“…The authors exploit floor information obtained from Wi-Fi data to calibrate barometer pressurebased floor detection. Another system that utilized barometric pressure data fused with Wi-Fi to determine the floor level is proposed in [26]. They used XGBoost to detect floor switching based on gyroscope and accelerometer signals.…”
Section: Related Workmentioning
confidence: 99%
“…Let us assume that the received signal strength of j-th access point in i-th reference point is indicated with 𝑟𝑠𝑠 𝑖,𝑟 𝑗 . Our proposed data preparation process consists of three steps: Following the result reported in [26], how Wi-Fi data is displayed affects the positioning accuracy rate. The authors indicated that powered representation of RSS ( 6) is more effective than linear and exponential representations.…”
Section: Access Point Adaptive Data Scalingmentioning
confidence: 99%
“…To overcome variable environmental effects, the floor information from the AP distribution helps initialize and calibrate the barometer for floor identification. Huang et al [185] studied floor localization in complex environments with atriums and large hollow areas. The authors combined WiFi and the barometer with a Hidden Markov Model (HMM) and XGBoost for floor estimation.…”
Section: F Hybrid Systemsmentioning
confidence: 99%